Metabolomics characterization of Senna tora (L.) Roxb. using different approaches - Kabila, Bhavna; Sidhu, M. C.; Ahluwalia, A. S. (Journal of Phytology, 2022)
The present study aimed to investigate the variety of elements, chemical compounds and their corresponding functional groups in the whole plant, leaves, and seeds of Senna tora. A preliminary phytochemical analysis has revealed the presence of secondary metabolites including alkaloids, flavonoids, tannins, terpenoids, cardiac active glycosides, phenolics, etc. Gas Chromatography and Mass Spectrophotometry (GC-MS) analysis of leaves and seeds of S. tora has depicted 31 and 27 compounds, respectively. Fourier Transform Infrared (FT-IR) Spectroscopy has further unveiled the presence of different functional groups such as amines, aromatic compounds, carboxyl groups, ketones etc. associated with different metabolites. Wavelength Dispersive X-ray Fluorescence (WD-XRF) has revealed the presence of more than 20 elements (macro and micro) including Ca, Mg, Fe, K, etc. This study has highlighted the detailed account of the chemical compounds and elements present in the plant species under investigation and substantiated its medicinal importance in the traditional health care system.